2019
DOI: 10.1186/s40168-019-0772-9
|View full text |Cite
|
Sign up to set email alerts
|

The subway microbiome: seasonal dynamics and direct comparison of air and surface bacterial communities

Abstract: BackgroundMass transit environments, such as subways, are uniquely important for transmission of microbes among humans and built environments, and for their ability to spread pathogens and impact large numbers of people. In order to gain a deeper understanding of microbiome dynamics in subways, we must identify variables that affect microbial composition and those microorganisms that are unique to specific habitats.MethodsWe performed high-throughput 16S rRNA gene sequencing of air and surface samples from 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 47 publications
5
59
0
Order By: Relevance
“…In winter, windows in kindergarten A are commonly closed to keep the classrooms warm. The classrooms in kindergartens A and B are about 9.9*9.8*3.6 m 3 and are larger than those in kindergarten C, which are about 6.1*5.8*2.8 m 3 . In spring, the windows in kindergarten A are also usually closed to maintain a comfortable environment of recycled air using an air conditioner.…”
Section: Sampling Locationsmentioning
confidence: 86%
See 2 more Smart Citations
“…In winter, windows in kindergarten A are commonly closed to keep the classrooms warm. The classrooms in kindergartens A and B are about 9.9*9.8*3.6 m 3 and are larger than those in kindergarten C, which are about 6.1*5.8*2.8 m 3 . In spring, the windows in kindergarten A are also usually closed to maintain a comfortable environment of recycled air using an air conditioner.…”
Section: Sampling Locationsmentioning
confidence: 86%
“…Only one colony was classified as Bacteroidetes (Weeksella virosa), which appeared in the 3 rd -stage plate (bacterial particle size range: 3.1 to 4.7 µm) from sampling round 4 (spring) at kindergarten C. The four phyla in the air samples (Table 1; Fig. 1) were the four most abundant phyla in the Oslo subway (air samples) [3] and a kindergarten in Oslo (floor dust samples) [6], but in a different order of relative abundance.…”
Section: Phylum-level Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial subway surfaces have been characterized previously in New York, Boston, Oslo, and México City (Afshinnekoo et al, 2015;Hsu et al, 2016;Gohli et al, 2019;Hernández et al, 2019). Additionally, the hand microbiome has been explored for Hong Kong subway passengers (Kang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There are culture-independent studies of subway surfaces of New York City (Afshinnekoo et al, 2015), Boston (Hsu et al, 2016), Oslo (Gohli et al 2019), Mexico City (Hernández et al 2019), and by MetaSUB (MetaSUB International Consortium, 2016), an international initiative. Such studies have shown that the subway microbiome is structured mostly by commensal bacteria from the skin and that microbial composition and diversity vary according to the material and type of usage.…”
Section: Introductionmentioning
confidence: 99%